DILEMA PERAN KELOMPOK HAJI DALAM PENGUATAN TRADISI BUDAYA DAN SOSIAL KEAGAMAAN: STUDI KASUS MASYARAKAT SUNGAI NYAMUK SEBATIK - Humaedi, Muhammad Alie (P2KK LIPI, 2013)
The Role of Haji Group Dilemma in Cultural Traditions and Social Religious Strengthening: Case Studies of Sungai Nyamuk-Sebatik Community Sebatik East Kalimantan is a variety of ethnic enclaves in Indonesia-Malaysia border. It builts not by an ethnic group, but filled with multiethnic carrying their own religions and values of its own internalization. Unfortunately, to reduce or prevent latent conflict, nullifying the violation of customary and religious can not be prevented by their religious leaders. The Hajj groups role were dysfunctional in people’s real life. This paper questioned the dysfunctional role of the hajj groups in strengthening social and religious traditions in Sungai Nyamuk Sebatik society? What is the motive exactly behind it dysfunctional role of the hajj groups. The answers will reveal to the extent religious values and traditions internalized and implemented in the understanding and practice patterns of life. In addition this writing will also unravel the internalization of religion as well as the real driving integrating motive could encourage the growth of social participation Keywords: Sungai Nyamuk Sebatik, role dysfunction, culture tradition, Hajj Groups